How can Problem-Posing foster meaningful learning experiences for EFL ninth graders? (2017)
ABSTRACT: This action research was designed to determine the effects of the implementation of Problem-posing and how it leads to meaningful learning experiences on the students from the ninth grade in a public institution in San Javier. The data was gathered though teacher journal, Cooperating teacher’s observation card as well as students’ feedback cards. The analysis and interpretations of the data indicated some positive outcomes of the implementation of a Problem-Posing unit as students were able to relate to the problem and think beyond it. Furthermore, some challenges were identified for both the teacher and the researcher in terms of the planning and language required respectively when following a Problem-posing Approach.